Fuel cell catalyst and method for producing same
The controlled synthesis and washing process for Pt nanowires on a carrier surface addresses aggregation and contamination issues, enhancing catalytic activity and durability in fuel cells.
Patent Information
- Application Number
- JP2021063103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-01
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-04-01
AI Technical Summary
Existing methods for supporting Pt nanowires on a carrier surface result in aggregation, low catalytic activity, and contamination due to metal ion elution, with non-uniform particle sizes and high spherical particle content.
A method involving controlled synthesis and washing processes to produce Pt nanowires with specific dimensions and low spherical particle content, supported at high density on a conductive carrier, using optimized temperature and solvent washing to minimize aggregation and contamination.
The method achieves high electrochemical surface area and mass activity, reducing catalyst poisoning and metal ion contamination, resulting in a highly active and durable fuel cell catalyst.
Smart Images

Figure 0007600832000003 
Figure 0007600832000004 
Figure 0007600832000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a fuel cell catalyst and a manufacturing method thereof, and more particularly to a fuel cell catalyst in which Pt-containing nanowire particles are densely supported on the surface of a support, and a manufacturing method thereof. [Background technology]
[0002] A polymer electrolyte fuel cell comprises a membrane electrode assembly (MEA) in which electrodes (catalyst layers) containing a catalyst are bonded to both sides of an electrolyte membrane. A gas diffusion layer is usually disposed on the outside of the catalyst layer. A current collector (separator) having a gas flow path is also disposed on the outside of the gas diffusion layer. A polymer electrolyte fuel cell usually comprises a structure (fuel cell stack) in which a plurality of unit cells each consisting of such an MEA, gas diffusion layer, and current collector are stacked.
[0003] The electrode catalyst for a polymer electrolyte fuel cell is usually one in which catalyst particles are supported on the surface of a carrier. The catalyst particles are made of precious metals such as Pt, Pd, Ru, or alloys containing these metals. Since the electrode reaction occurs on the surface of the catalyst particles, if fine catalyst particles are supported on the surface of the carrier in a highly dispersed manner, the utilization rate of the precious metal is improved, and the amount of expensive precious metal used can be reduced. Therefore, various methods for producing and supporting fine catalyst particles have been proposed.
[0004] For example, Non-Patent Document 1 states: (a) Pt(acac) 2 , Ni(acac) 2 , cetyltrimethylammonium chloride (CTAC), and Mo(CO) 6 is dissolved in oleylamine (OA), (b) Heat the resulting homogeneous solution in an oil bath at 160°C for 2 hours; (c) The colloidal product was collected by centrifugation and washed three times with a mixture of cyclohexane / ethanol (1:9, v / v). A method for producing Pt nanowires is disclosed.
[0005] Furthermore, Non-Patent Document 1 states: (a) supporting the thus obtained Pt nanowires on a carbon support surface; (b) Wash the Pt nanowires / C three times with a cyclohexane / ethanol mixture. A catalyst obtained by the above process is disclosed.
[0006] The same document states: (A) such a method results in Pt nanowires with diameters of 0.8 nm and aspect ratios of about 22.5; and (B) The mass activity (MA), specific activity (SA), and electrochemically effective surface area (ECSA) of Pt nanowires / C are 1.06 A / mg and 1.39 mA / cm, respectively. 2 , and 76.4m 2 / g, is stated.
[0007] Pt nanowires can be synthesized by using the method described in Non-Patent Document 1. However, the method described in Non-Patent Document 1 does not allow Pt nanowires to be supported on the support surface at a high loading density without agglomerating the Pt nanowires. In addition, the Pt nanowire / C catalyst obtained by the method described in Non-Patent Document 1 has a relatively low catalytic activity. Also, Ni(acac) 2 Ni compounds such as these are necessary components for the high activity of nanowire catalysts through alloying effects and surface control, but Ni or Ni compounds may remain in the catalyst depending on the manufacturing conditions. Ni alloyed with Pt has the effect of improving the catalytic activity of Pt, but Ni, Ni compounds, and Ni alloyed with Pt contained in the catalyst are easily eluted in the fuel cell environment and cause cationic contamination.
[0008] Furthermore, in the method described in Non-Patent Document 1, if the addition of the Ni compound is omitted, Pt nanowires that do not contain Ni are generated. However, in the method described in the same document, simply omitting the addition of the Ni compound does not result in Pt nanowires with uniform short and long diameters. In addition, there is a problem in that, in addition to Pt nanowires, a relatively large amount of spherical particles containing Pt is by-produced. [Prior art documents] [Non-patent literature]
[0009] [Non-Patent Document 1] Kezhu Jiang et al., Sci. Adv. 2017;3:e1601705 Summary of the Invention [Problem to be solved by the invention]
[0010] The problem that the present invention aims to solve is to provide a fuel cell catalyst and a method for producing the same, in which Pt-containing nanowire particles are densely supported on the surface of a support, there is little aggregation of the nanowire particles, there is little decrease in activity due to catalyst poisoning, and there is little Pt-containing spherical particles. Another object of the present invention is to provide a fuel cell catalyst which causes less elution of metal ions, and a method for producing the same. [Means for solving the problem]
[0011] In order to solve the above problems, the fuel cell catalyst according to the present invention has the following configuration. (1) The fuel cell catalyst is A conductive carrier; nanowire particles containing Pt supported on the support surface; It is equipped with: (2) The nanowire particles are The minor axis d is 0.8 nm or more and 10.0 nm or less, The loading rate is 15 mass% or more and 50 mass% or less. (3) The fuel cell catalyst has a content of Pt-containing spherical particles (= the ratio of the number of the spherical particles to the total number of the nanowire particles and the spherical particles) of 10% or less.
[0012] The method for producing a fuel cell catalyst according to the present invention has the following features. (1) The method for producing the fuel cell catalyst comprises the steps of: Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dissolving or dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; a second step of obtaining nanowire particle precursors, the surfaces of which are modified with the oleylamine, by maintaining the precursor solution at 100° C. or higher and 120° C. or lower; a third step of washing the nanowire particle precursor to obtain the nanowire particles from which a portion of the oleylamine modifying the surface has been removed; a fourth step of supporting the nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the nanowire particles supported on the surface of the support; a fifth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the nanowire particles, thereby obtaining a fuel cell catalyst according to the present invention; It is equipped with: (2) The third step comprises washing the nanowire particle precursor once with ethanol or a cyclohexane / ethanol mixed solvent. (3) The fifth step comprises washing the catalyst precursor three or more times with a solvent consisting of at least one selected from the group consisting of hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins. The first step may further comprise dissolving or dispersing a base metal element precursor in the oleylamine. Effect of the Invention
[0013] When nanowire particles containing Pt are synthesized from a Pt precursor, if they are synthesized at a relatively low temperature, nanowire particles containing a small amount of spherical particles containing Pt can be obtained.
[0014] Furthermore, if the nanowire particles are synthesized and then washed relatively weakly, the surface modifier oleylamine is not excessively removed, thereby preventing the nanowire particles from agglomerating, and the nanowire particles can be densely supported on the support surface without agglomerating. Furthermore, after the nanowire particles are supported on the support surface, the remaining surface modifier can be almost completely removed by performing a relatively strong washing, thereby suppressing catalyst poisoning caused by the remaining surface modifier. [Brief description of the drawings]
[0015] [Figure 1] 1 is a STEM image of the nanowire particles obtained in Example 1. [Diagram 2] 1 is a STEM image of the nanowire particles obtained in Example 2. [Diagram 3] 2 is a STEM image of the nanowire particles obtained in Comparative Example 1. [Figure 4] 1 is a STEM image of the fuel cell catalyst obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An embodiment of the present invention will be described in detail below. [1. Fuel cell catalyst] The fuel cell catalyst according to the present invention (hereinafter, simply referred to as "catalyst") is A conductive carrier; nanowire particles containing Pt supported on the support surface; It is equipped with:
[0017] 1.1. Carrier The carrier is made of a conductive material. There is no particular limitation on the material of the carrier, so long as it is conductive and usable in the fuel cell operating environment. Examples of the material of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.
[0018] [1.2. Nanowire particles] [1.2.1. Shape] In the present invention, the term "nanowire particles" refers to particles having a wire-like elongated shape and a diameter in the nanometer range. By using the method described below, nanowire particles having a short diameter of more than 0.8 nm and not more than 10 nm, or more than 0.8 nm and not more than 5.0 nm, can be obtained. When the manufacturing conditions are optimized, the short diameter becomes greater than 0.8 nm and equal to or less than 3 nm. Similarly, when the manufacturing conditions are optimized, the length is 5 nm or more and 50 nm or less.
[0019] [1.2.2. Composition] In the present invention, the nanowire particles contain Pt. By using the method described below, nanowire particles having a Pt content of 90 mass% or more can be obtained. By optimizing the production conditions, the Pt content can be 95 mass% or more, or 98 mass% or more. Impurities that may be contained in nanowire particles include, for example, metal elements (eg, Ni, Mo, W, etc.) derived from the starting material.
[0020] [1.2.3. Loading rate] "Supporting ratio" refers to the ratio of the mass of nanowire particles to the total mass of the catalyst. In general, if the loading rate is too low, the amount of Pt per unit volume when a membrane electrode assembly (MEA) is produced will be small. Therefore, the thickness of the catalyst layer required to ensure a sufficient amount of Pt for power generation will be large. In general, the thicker the catalyst layer, the greater the resistance to mass transfer within the catalyst layer. Therefore, the loading rate must be 15 mass% or more. The loading rate is preferably 20 mass% or more, and more preferably 30 mass% or more. On the other hand, even if the loading rate is increased more than necessary, there is no difference in the effect and no practical benefit. Therefore, the loading rate must be 50 mass% or less.
[0021] [1.3. Characteristics] [1.3.1. Content of spherical particles containing Pt] "Spherical particles containing Pt" refers to particles whose main component is Pt (particles with a Pt content of 90 mass % or more) that are produced as a by-product during the synthesis of nanowire particles and have an aspect ratio of 1.1 or less. "Spherical particle content" refers to the ratio of the number of spherical particles to the total number of nanowire particles and spherical particles contained in the field of view when the synthesized nanowire particles are observed under a microscope at a magnification at which 50 or more nanowire particles are observed in the field of view.
[0022] The nanowire particles according to the present invention are synthesized using the method described below, and therefore contain less spherical particles than conventional nanowire particles. When the manufacturing conditions are optimized, the spherical particle content is 10% or less. When the manufacturing conditions are further optimized, the spherical particle content is 5% or less, or 3% or less.
[0023] [1.3.2. ECSA (effective electrochemical surface area)] The fuel cell catalyst according to the present invention exhibits high ECSA because nanowire particles are densely supported on the support surface and the nanowire particles are less likely to aggregate. When the production conditions are optimized, the ECSA can reach 40m. 2 / g Pt More than 200m 2 / g PtFurther optimization of the production conditions results in a catalyst with an ECSA of 70m 2 / g Pt or more than 100m 2 / g Pt That's all.
[0024] [1.3.3. MA (activity per Pt mass)] The nanowire particles have a diameter of nanometer size, a large surface area per Pt mass, and a high density of highly active (111) faces, so they exhibit high MA. When the manufacturing conditions were optimized, the MA was increased to 900 A / g Pt More than 30000A / g Pt Further optimization of the preparation conditions results in a catalyst with an MA of 1000 A / g or less. Pt That's all.
[0025] [1.3.4. SA (specific activity)] The fuel cell catalyst according to the present invention exhibits high SA. When the production conditions are optimized, the SA can reach 2000 μA / cm 2 More than 15000μA / cm 2 Further optimization of the production conditions results in a catalyst with an SA of 2500 μA / cm 2 That's all.
[0026] [1.3.5. Base metal element content] The "content of base metal elements" refers to the ratio of the mass of base metal elements to the total mass of the catalyst. When synthesizing nanowire particles containing Pt, Ni(acac) 2 By adding a base metal element precursor such as the above, nanowire particles consisting of an alloy of Pt and the base metal element can be synthesized. Using a base metal element may enable the nanowire particles to be highly activated due to the alloying effect and surface control. However, when a base metal element precursor is used in the synthesis of nanowire particles, unreacted base metal element precursor, or compounds of the base metal element or fine particles of the base metal element produced by the decomposition and reaction of the base metal element precursor may be mixed into the nanowire particles.
[0027] Base metal elements alloyed with Pt can improve the catalytic activity of Pt, but the base metal element particles and compounds mixed in the nanowire particles, as well as the base metal elements alloyed with Pt, can all easily dissolve in the fuel cell environment and cause cationic contamination. In contrast, when the method described below is used, a catalyst with a base metal element content of less than 0.01 mass % can be obtained. When the production conditions are optimized, the base metal element content can be reduced to 0.005 mass % or less.
[0028] [2. Manufacturing method of fuel cell catalyst] The method for producing a fuel cell catalyst according to the present invention includes the steps of: Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dissolving or dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; a second step of obtaining nanowire particle precursors, the surfaces of which are modified with the oleylamine, by maintaining the precursor solution at 100° C. or higher and 120° C. or lower; a third step of washing the nanowire particle precursor to obtain the nanowire particles from which a portion of the oleylamine modifying the surface has been removed; a fourth step of supporting the nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the nanowire particles supported on the surface of the support; a fifth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the nanowire particles, thereby obtaining a fuel cell catalyst according to the present invention; It is equipped with:
[0029] [2.1. 1st step] First, the Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a nitrogen-containing surfactant are dissolved or dispersed in oleylamine to obtain a precursor solution (first step). The first step may further comprise dissolving or dispersing a base metal element precursor in the oleylamine.
[0030] 2.1.1. Ingredients The Pt precursor is the main raw material of the nanowire particles. The type of Pt precursor is not particularly limited as long as it can synthesize the nanowire particles. Examples of Pt precursors include platinum(II) acetylacetonate (Pt(acac) 2 ), chloroplatinic acid (H 2 PtCl 6 ), tetraammineplatinum chloride (Pt(NH 3 ) 4 Cl 2 ) etc.
[0031] W(CO) 6 and Mo(CO) 6 is a component necessary for controlling the length and surface roughness of nanowire particles. The precursor solution contains W(CO) 6 or Mo(CO) 6 Either one of them may be included, or both may be included. The precursor solution is W(CO) 6 and / or Mo(CO) 6 When W(CO) is added, 6 Also Mo(CO) 6 CO is released from the nanowire. The released CO is repeatedly adsorbed and desorbed on the surface of the nanowire particle during growth. As a result, it is thought that the length of the nanowire particle and the surface roughness are controlled.
[0032] Nitrogen-containing surfactants are necessary components for growing Pt into wires. When nitrogen-containing surfactants are added to the precursor solution, rod-like micelles are generated, and it is believed that nanowire particles are generated by reducing the Pt precursor within the rod-like micelles. The type of nitrogen-containing surfactant is not particularly limited as long as it is capable of synthesizing nanowire particles. Examples of nitrogen-containing surfactants include cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), and dodecyltrimethylammonium bromide (DDAB).
[0033] The base metal element precursor is an effective component for high activation of nanowire particles and can be added as necessary. The addition of a strong reducing agent (e.g., sodium borohydride (NaBH)) to the precursor solution is also effective. 4 When the base metal element precursor is not contained, the base metal element precursor is not usually reduced, and nanowire particles consisting essentially of Pt are obtained. However, depending on the synthesis conditions, base metal elements or compounds of base metal elements may be by-produced. The type of base metal element precursor is not particularly limited as long as it is capable of synthesizing nanowire particles. For example, an example of a base metal element precursor containing Ni is Ni(II) acetylacetonate (Ni(acac) 2 ), Nickel chloride (NiCl 2 ), nickel acetate (Ni(CH 3 COO) 2 ) etc.
[0034] Oleylamine is (a) a solvent for dissolving the raw materials; (b) a reducing agent for reducing the Pt precursor, and (c) A surface modifier that adsorbs to the surface of nanowire particles and prevents the nanowire particles from agglomerating. It functions as: However, since the reducing power of oleylamine is relatively weak, the reduction of the Pt precursor proceeds, but other substances (e.g., Ni(caca) 2 The reduction of base metal elements (precursors of base metal elements such as Cr, Fe, and Fe) usually does not proceed very well.
[0035] [2.1.2. Concentration] The concentration of each component contained in the precursor solution is not particularly limited, and an optimal concentration can be selected depending on the purpose. Generally, if the concentration of the Pt precursor is too low, the yield of nanowire particles is low, so the concentration of the Pt precursor is preferably 0.24 mass% or more. On the other hand, even if the concentration of the Pt precursor is made higher than necessary, there is no difference in the effect and no practical benefit, so the concentration of the Pt precursor is preferably 0.48 mass% or less.
[0036] In general, W(CO) 6 and Mo(CO) 6 If the total concentration of W(CO) is too low, nanowire particles cannot be recovered. 6 and Mo(CO) 6 The total concentration is preferably 0.07 mass% or more. On the other hand, W(CO) 6 and Mo(CO) 6 Even if the total concentration of W(CO) is increased more than necessary, there is no difference in the effect and no practical benefit. 6 and Mo(CO) 6 The total concentration is preferably 0.7 mass% or less.
[0037] In general, the higher the concentration of the nitrogen-containing surfactant, the easier it is to form rod-like micelles, which in turn makes it easier for Pt to grow into nanowires. To achieve this effect, the concentration of the nitrogen-containing surfactant is preferably 0.39 mass% or more. On the other hand, if the concentration of the nitrogen-containing surfactant is made higher than necessary, there is no difference in the effect and no practical benefit, and therefore the concentration of the nitrogen-containing surfactant is preferably 3.0 mass% or less.
[0038] In the case of adding a base metal element precursor to the raw material, generally, if the concentration of the base metal element precursor is too low, the high activation of the nanowire particles due to the alloying effect and surface control may not be obtained. Therefore, the concentration of the base metal element precursor is preferably 0.01 mass% or more. On the other hand, if the concentration of the base metal element precursor is too high, the amount of the base metal element that is reduced increases, so the concentration of the base metal element precursor is preferably 0.15 mass% or less.
[0039] [2.2. 2nd process] Next, the precursor solution is held at a temperature of 100° C. or more and 120° C. or less (second step), thereby obtaining nanowire particle precursors in which the surfaces of the nanowire particles are modified with oleylamine.
[0040] If the treatment temperature is too low, the reduction reaction will not proceed within a practical time period, so the treatment temperature is preferably 100° C. or higher. On the other hand, if the treatment temperature is too high, a relatively large amount of spherical particles are produced as by-products, so the treatment temperature is preferably 120° C. or lower.
[0041] If the treatment time is too short, the yield of nanowire particles decreases. Therefore, the treatment time is preferably 2 hours or more, more preferably 4 hours or more, and even more preferably 8 hours or more. On the other hand, if the treatment time is longer than necessary, there is no difference in the effect and no practical benefit, so it is preferable to select an optimal treatment time depending on the purpose.
[0042] [2.3. Third step] Next, the nanowire particle precursor is washed to obtain nanowire particles from which a portion of the oleylamine modifying the surface has been removed (third step).
[0043] Oleylamine is a necessary component for forming nanowire particles, but it is also a substance that poisons the active sites of the catalyst. In order to reduce catalyst poisoning, it is preferable to completely remove oleylamine from the surface of the nanowire particles. However, oleylamine also functions as a surface modifier that suppresses the aggregation of nanowire particles generated in the solution. Therefore, if the nanowire particles are washed under conditions that remove all of the oleylamine that modifies the surface of the nanowire particles before they are supported on the support surface after the reaction is completed, the nanowire particles are likely to aggregate.
[0044] Therefore, the washing before loading the nanowire particle precursor on the carrier surface must be performed under conditions that remove by-products and unreacted materials and also remove a portion of the oleylamine modifying the surface of the nanowire particle. In the present invention, the washing before loading is performed only once with ethanol or a cyclohexane / ethanol mixed solvent. This is different from the conventional method. Ethanol and cyclohexane / ethanol mixed solvents both have a moderate cleaning power, so washing with ethanol or cyclohexane / ethanol mixed solvents multiple times will remove too much oleylamine. Therefore, washing before loading is performed only once.
[0045] When using a cyclohexane / ethanol mixed solvent as a cleaning solvent, the content of cyclohexane in the mixed solvent is selected to be optimal depending on the purpose. In general, the higher the cyclohexane content, the stronger the cleaning power. To obtain such an effect, the cyclohexane content is preferably 10 vol% or more. On the other hand, even if the content of cyclohexane is increased more than necessary, there is no difference in the effect and no practical benefit, so the content of cyclohexane is preferably 50 vol% or less.
[0046] [2.4. 4th step] Next, the nanowire particles are supported on the surface of a conductive support (fourth step), thereby obtaining a catalyst precursor having the nanowire particles supported on the surface of the support. The method of supporting nanowire particles on the carrier surface is not particularly limited. For example, when the nanowire particle precursor and the carrier are dispersed in a solvent and ultrasonic waves are applied, the nanowire particle precursor and the carrier are uniformly dispersed, and at the same time, the oleylamine on the nanowire particle surface is gradually removed by the solvent. Furthermore, when most of the oleylamine on the nanowire particle surface is removed, the nanowire particles are attached onto the carrier. As a result, the nanowire particles can be supported on the carrier surface.
[0047] [2.5. 5th step] Next, the catalyst precursor is washed to further remove any oleylamine remaining on the surfaces of the nanowire particles (step 5), thereby obtaining the fuel cell catalyst according to the present invention.
[0048] As mentioned above, oleylamine is a surface modifier for suppressing aggregation, and at the same time, it is also a substance that causes catalyst poisoning. In order to reduce catalyst poisoning, it is preferable to wash the nanowire particles after they are supported on the support surface under conditions that allow the oleylamine remaining on the surface of the nanowire particles to be almost completely removed. "Almost completely removed" means that the SA of the catalyst after washing is 2000 μA / cm 2 This means that the above is the case. In the present invention, the catalyst precursor is washed three or more times after the loading with a solvent consisting of at least one selected from the group consisting of hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins, which is different from the conventional method.
[0049] Hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins all have stronger cleaning power than the cyclohexane / ethanol mixed solvent, so washing the catalyst precursor with these solvents can remove most of the remaining oleylamine. The above solvents have strong cleaning power, so that a sufficient effect can be obtained even with one cleaning. However, generally, the more the number of cleanings, the less the amount of oleylamine remaining. In order to reduce catalyst poisoning, the number of cleanings must be three or more. The number of cleanings is preferably five or more. When a base metal element precursor is added to the raw material, after the strong washing, an acid washing may be further performed to remove excess base metal elements remaining in the nanowire particles.
[0050] [3. Effect] [3.1. Suppression of spherical particle formation] As described in Non-Patent Document 1, Ni(acac) was used in the synthesis of Pt nanowires. 2 When added to the raw materials, nanowires made of Pt-Ni alloy can be synthesized. However, although Ni has the effect of improving the catalytic activity of Pt, Ni alloyed with Pt easily dissolves in the fuel cell environment and becomes a cause of cationic contamination. On the other hand, in the method described in Non-Patent Document 1, Ni(acac) 2 If the use of Ni is omitted, Pt nanowires that do not contain Ni are produced. However, in the method described in the document, simply omitting the use of Ni compounds does not result in Pt nanowires with uniform short and long diameters. In addition to Pt nanowires, there is a problem in that a relatively large amount of spherical particles containing Pt are produced as a by-product. This is thought to be due to the high reaction temperature (160°C), which tends to destabilize the micelles of the surfactant.
[0051] In contrast, when synthesizing nanowire particles containing Pt from a Pt precursor at a relatively low temperature (specifically, 100° C. to 120° C.), nanowire particles containing a small amount of spherical particles containing Pt can be obtained.
[0052] When synthesizing nanowire particles containing Pt, if no base metal element precursor is used, there is no need to reduce the base metal element precursor. Therefore, the reduction of the Pt precursor can be completed even if the reaction temperature is lower than when synthesizing a Pt alloy. However, when the reaction temperature is lowered, the reaction time must be extended to complete the reduction reaction of the Pt precursor. On the other hand, lowering the reaction temperature stabilizes the micelles of the surfactant during nanowire formation, resulting in nanowire particles with smaller minor axis size, smaller minor axis size variation, and a smaller content of spherical particles.
[0053] When such nanowire particles are highly dispersed on the surface of a support, a catalyst with high activity can be obtained because of the large reaction area. In addition, because the particle diameter is uniform, a catalyst with a low reaction area loss due to Ostwald grain growth can be obtained. Furthermore, when such a catalyst is applied to a fuel cell, the performance of the fuel cell is improved.
[0054] [3.2. Suppression of nanowire particle aggregation] Oleylamine functions as a surface modifier that prevents the aggregation of nanowire particles. After synthesizing nanowire particles in the presence of oleylamine, washing the nanowire particles three times with a cyclohexane / ethanol mixed solvent results in excessive removal of oleylamine from the nanowire particle surface. This makes it difficult to suppress the aggregation of nanowire particles, and makes it difficult to support nanowire particles on the support surface at high density and high dispersion.
[0055] Next, even if the nanowire particles are supported on the support surface and washed three times with a cyclohexane / ethanol mixed solvent, the oleylamine remaining on the surface of the nanowire particles cannot be completely removed. The remaining oleylamine blocks (poisons) the active sites of the catalyst, causing a decrease in catalytic activity.
[0056] In contrast, if the nanowire particles are synthesized and then washed relatively weakly, the surface modifier oleylamine is not removed excessively, thereby suppressing the aggregation of the nanowire particles, and the nanowire particles can be densely supported on the support surface without agglomeration. In addition, by performing relatively strong washing after supporting the nanowire particles on the support surface, the remaining surface modifier can be almost completely removed, thereby suppressing catalyst poisoning caused by the remaining surface modifier. EXAMPLES
[0057] (Examples 1 to 2, Comparative Example 1) [1. Sample preparation] [1.1. Examples 1 to 2] Pt(acac) 2 , Mo(CO) 6 and a nitrogen-containing surfactant were added to oleylamine and ultrasonically dispersed for 1 hour to obtain a precursor solution. This precursor solution was heated from room temperature to the reaction temperature at a rate of 10°C / min and held at the reaction temperature for 8 hours. The reaction temperature was 100°C (Example 1) or 120°C (Example 2). The temperature was then lowered to room temperature to obtain a colloidal solution in which Pt-containing nanowire particles were dispersed. The nanowire particles were collected from the colloidal solution and washed once with ethanol to remove unreacted materials and a portion of the surface modifier (oleylamine).The colloidal solution was then centrifuged to collect the nanowire particles.
[0058] Next, the washed nanowire particles were redispersed in hexane to obtain Dispersion A. Furthermore, the carbon support was dispersed in hexane to obtain Dispersion B. Dispersion A was added to Dispersion B, and ultrasonic waves were applied for 1 hour to support the nanowire particles on the carbon support surface. Furthermore, the nanowire particle-supported carbon (hereinafter also referred to as "nanowire particle / C") was recovered from the dispersion and the nanowire particle / C was washed five times with hexane. The solid matter was then filtered and dried to obtain a catalyst.
[0059] [1.2. Comparative Example 1] A catalyst was obtained in the same manner as in Example 1, except that the reaction temperature of the precursor solution was 160° C. and the retention time at the reaction temperature was 2 hours.
[0060] 2. Test Method [2.1. STEM observation] The nanowire particles before being supported on the carbon support and the nanowire particle / C were observed using a scanning transmission electron microscope (STEM).
[0061] [2.2. Electrochemical evaluation] [2.2.1. Mass activity] The catalyst was electrochemically evaluated using a rotating disk electrode (RDE). The cell was a three-electrode type, and the electrolyte was 0.1M HClO4 The working electrode was made of glassy carbon coated with a catalyst. The reference electrode and counter electrode were a reversible hydrogen electrode (RHE) and a black Pt mesh, respectively. The working electrode was immersed in an electrolyte saturated with Ar, and a potential sweep was performed between 0.05 V and 1.2 V (RHE). The potential sweep was performed until the shape of the cyclic voltammogram (CV) became stable. The electrolyte was then replaced with O 2 The electrodes were saturated with 1000 volts of platinum and rotated at 1600 rpm while linear sweep voltammetry (LSV, positive potential sweep, sweep rate: 10 mV / s) was performed. The mass activity (MA) of each sample was calculated by dividing the obtained LSV current value at 0.9 V by the platinum mass.
[0062] [2.2.2. Durability test] After the initial activity evaluation, a durability test was performed. The durability test was performed in an oxygen-saturated electrolyte (0.1M HClO 4 ) was subjected to 2000 cycles of potential sweep from 0.4 V to 1.0 V (based on RHE, held at each potential for 3 s). For each sample, the mass activity (MA) at 0.9 V was determined before and after the durability test. 0 The ratio of mass activity (MA) after durability test to mass activity (MA) (=MA × 100 / MA 0 ) was calculated as the activity retention rate.
[0063] [3. Results] [3.1. TEM Observation] Figure 1 shows a STEM image of the nanowire particles obtained in Example 1. Figure 2 shows a STEM image of the nanowire particles obtained in Example 2. Figure 3 shows a STEM image of the nanowire particles obtained in Comparative Example 1. Figure 4 shows a STEM image of the fuel cell catalyst (nanowire particles / C) obtained in Example 1. Furthermore, Table 1 shows the content of spherical particles. 1 to 4 and Table 1 show that the nanowire particles of Examples 1 and 2 have a more uniform minor axis than the nanowire particles of Comparative Example 1, and have a smaller content of spherical particles.
[0064] [Table 1]
[0065] [3.2. Electrochemical evaluation] Table 2 shows the initial mass activity, mass activity after the durability test, and mass activity retention rate of the nanowire particles / C obtained in Example 2 and Comparative Example 1. It can be seen from Table 2 that the mass activity and mass activity retention rate of Example 2 are greater than those of Comparative Example 1. In other words, it was found that the use of the method according to the present invention makes it possible to obtain a highly active and highly durable catalyst.
[0066] [Table 2]
[0067] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0068] The fuel cell catalyst according to the present invention can be used as an electrode catalyst for the air electrode and / or fuel electrode of a polymer electrolyte fuel cell used in, for example, a power source for an automobile or a small stationary generator.
Claims
1. A fuel cell catalyst comprising: (1) The fuel cell catalyst is A conductive carrier; nanowire particles including Pt supported on the support surface; It is equipped with: (2) The nanowire particles are The minor axis d is 0.8 nm or more and 10.0 nm or less, The length is 5 nm or more and 50 nm or less, The loading rate is 15 mass % or more and 50 mass % or less. (3) The fuel cell catalyst is the content of the spherical particles containing Pt (= the ratio of the number of the spherical particles to the total number of the nanowire particles and the spherical particles) is 10% or less, MA (activity per Pt mass) is 900 A / g Pt More than 30000A / g Pt The following is the result.
2. ECSA (effective electrochemical surface area) is 40m 2 / g Pt More than 200m 2 / g Pt 2. The fuel cell catalyst of claim 1, wherein:
3. SA (specific activity) is 2000 μA / cm 2 More than 15000μA / cm 2 3. The fuel cell catalyst according to claim 1, wherein:
4. 4. The fuel cell catalyst according to claim 1, wherein the content of base metal elements is less than 0.01 mass %.
5. A method for producing a fuel cell catalyst comprising the following steps: (1) The method for producing the fuel cell catalyst includes the steps of: Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dissolving or dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; a second step of obtaining nanowire particle precursors in which the surfaces of nanowire particles are modified with the oleylamine by maintaining the precursor solution at 100° C. or higher and 120° C. or lower; a third step of washing the nanowire particle precursor to obtain the nanowire particles from which a portion of the oleylamine modifying the surface has been removed; a fourth step of supporting the nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the nanowire particles supported on the surface of the support; a fifth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the nanowire particles, thereby obtaining the fuel cell catalyst according to any one of claims 1 to 4; It is equipped with: (2) The third step comprises washing the nanowire particle precursor once with ethanol or a cyclohexane / ethanol mixed solvent. (3) The fifth step comprises washing the catalyst precursor three or more times with a solvent consisting of at least one selected from the group consisting of hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins.
6. 6. The method for producing a fuel cell catalyst according to claim 5, wherein the first step further comprises dissolving or dispersing a base metal element precursor in the oleylamine.
Citation Information
Patent Citations
MANUFACTURING METHOD FOR Pt-Co ALLOY NANO WIRES CATALYST AND Pt-Co ALLOY NANO WIRES CATALYST
KR1020200099109A
Catalyst for a fuel cell, a method for preparing the same, and a membrane-electrode assembly for a fuel cell including the same
US20070099069A1
Ultrafine nanowires as highly efficient electrocatalysts
US20190226120A1
